Pelembagaan Partai Golkar Pasca Reformasi: Perbandingan Era Kepemimpinan Aburizal Bakrie dan Airlangga Hartarto - Malindir, Gaston; Nabila (Journal of Politics and Policy, 2025)
The purpose of this study is to compare the institutionalization of the Golkar Party during the leadership era of Aburizal Bakrie and Airlangga Hartarto. This study uses a qualitative approach with the data collection technique, namely the literature study. The results of this study indicate that; (1) Aburizal Bakrie's leadership was unsuccessful in increasing support at the grassroots level, as evidenced by a significant decline in votes in the 2014 Election. On the other hand, under Airlangga Hartarto's leadership, the Golkar Party managed to record a significant increase in votes in the 2024 Election, after the decline in 2019. (2) During Aburizal Bakrie's leadership, the Golkar Party was freer from external intervention, especially because of its non-involvement in the winning coalition for elections. Meanwhile, during Airlangga Hartarto's leadership, the intervention of power was increasingly is evident, especially in decision-making